Climate-induced involuntary migration: nomadic-pastoralists' search for elusive pastures in Kenya - Nabenyo, E (Refugee Studies Centre, University of Oxford, 2020)
As the impacts of climate change grow more severe, Turkana nomadic-pastoralists are increasingly being forced to move, rather than choosing to move. Their voices must be heard at the local and international level, and their knowledge and insights must inform policymaking.